Kompilasi Hukum Islam (KHI) Sejarah Penyusunan, Dasar dan Eksistensinya dalam Tata Urutan Perundang-Undangan ditinjau dari Politik Hukum Indonesia - Hendrayani; Saifullah; Tamrin Kamal; Desi Asmaret; Julhadi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The Compilation of Islamic Law (KHI) is a legal entity that emerged based on the need for a legal basis and reference for Muslims, especially for judges in the Religious Courts in Indonesia in deciding a case. The presence of the Compilation of Islamic Law (KHI), makes it easier for judges to make decisions, and these decisions become jurisprudence within the Indonesian Religious Courts. Before the presence of the Compilation of Islamic Law (KHI), judges took references from various classical books scattered across various schools of thought (Safi`I, Maliki, Hanafi, Hambali), so it is not uncommon for different decisions to occur in the same case. The Compilation of Islamic Law (KHI), although not yet equivalent to the Law, has received quite a positive response in meeting basic legal needs, especially in the fields of marriage, inheritance, zakat and wills in Indonesia. This article was written using the library research method, by looking at various books and literature and used as references. In this conclusion, it mentions history, matters regarding the Compilation of Islamic Law up to its position in the legal system and legislation in Indonesia.